2011
DOI: 10.1161/circulationaha.110.966846
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the 5-Lipoxygenase Pathway in Human Aortic Valves Correlates With Severity of Stenosis and Leads to Leukotriene-Induced Effects on Valvular Myofibroblasts

Abstract: Background-The development of aortic valve stenosis is not only associated with calcification and extracellular matrix remodeling, but also with inflammation. The aim of this study was to determine the role of proinflammatory signaling through the leukotriene (LT) pathway in aortic stenosis. Methods and Results-After macroscopic dissection of surgically removed human aortic valves, RNA was extracted from 311 preparations derived from 68 patients to differentiate normal, thickened, and calcified areas from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 48 publications
8
92
0
Order By: Relevance
“…These authors also demonstrated that a nuclear localization sequence (localized in the C tail) is essential for the receptor translocation to the nucleus, as already demonstrated for other GPCRs (Boivin et al, 2008) as well as for other proteins that normally target the nucleus, such as 5-LO (Hanaka et al, 2002). Finally, CysLT 1 R expression in myofibroblasts derived from human heart valves exhibits a perinuclear pattern, and LTC 4 increased nuclear [Ca 2ϩ ] in those cells (Nagy et al, 2011).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 57%
“…These authors also demonstrated that a nuclear localization sequence (localized in the C tail) is essential for the receptor translocation to the nucleus, as already demonstrated for other GPCRs (Boivin et al, 2008) as well as for other proteins that normally target the nucleus, such as 5-LO (Hanaka et al, 2002). Finally, CysLT 1 R expression in myofibroblasts derived from human heart valves exhibits a perinuclear pattern, and LTC 4 increased nuclear [Ca 2ϩ ] in those cells (Nagy et al, 2011).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 57%
“…Because these molecules were found to be co-localized with PLA2-IIE and -V in the aortic valves in the present study, eicosanoids may be produced within valve tissue and/or play a role in the development of valve calcification 1) . In line with the present findings, a previous report showed that the 5-LOX expression is increased in calcified human aortic valves and that the incubation of myofibroblast cultures with LTC4, a 5-LOX metabolite, induces calcium nodule formation 2) . In cultures of tendon stem cells, serotonergic receptor signals have been shown to stimulate tissuenonspecific ALP through the actions of eicosanoids produced via the PLA2 pathway 17) .…”
Section: Cultures Of Valve Interstitial Cells (Vics)supporting
confidence: 93%
“…Another report showed that PGE2 stimulates the osteogenic differentiation of cultured tendon stem cells via BMP-2 induction 18) . Taken together, these previous reports 2,17,18) appear to support the hypothesis that eicosanoids produced via the PLA2 pathway contribute to the process of ectopic osteogenesis in cardiac valves.…”
Section: Cultures Of Valve Interstitial Cells (Vics)supporting
confidence: 80%
See 1 more Smart Citation
“…Moreover they showed that leukotriene C4 (LTC4) increased intracellular calcium, enhanced reactive oxygen species production, reduced the mitochondrial membrane potential, and led to morphological cell cytoplasm changes and calcification. This data suggest the up-regulation of the pathway LT and the potentially detrimental LT-induced effects on valvular myofibroblasts as possible role in the development of aortic stenosi and induce to considerate innovative therapeutic interventions (42). The first landmark randomized, prospective trial published in this field, Scottish Aortic Stenosis and Lipid Lowering Trial, Impact on Regression (SALTIRE), (43) demonstrated, however, that high-dose atorvastatin does not slow the progression of this disease.…”
Section: Future Directions In Medical Treatmentmentioning
confidence: 99%